EFFECTIVENESS BETWEEN MEDIA VIDEO AND EDUCATIONAL GAMES ABOUT THE BEHAVIOR OF BRUSHING YOUR TEETH - Fitri, Elmalia (Journal of Applied Health Management and Technology, 2024)
Background: The causes of dental and oral health problems are behaviors, behaviors that often ignore dental and oral hygiene. In Indonesia, 94.7% of daily brushing behaviors were shown, but only 2.8% brushed their teeth at the correct time. One of the efforts in improving the degree of dental and oral health is by promoting or promoting health. In health promotion efforts to facilitate the delivery of messages or information is usually used by the media. Many media can be used, one of which is video media and educational games to help the delivery of information. Media is also included in socialization agents that can play a role in developing and influencing one's behavior. Method: This type of research is literature review research. The data used in literature review research is secondary data that can be obtained from various forms of literature. The secondary data source uses 3 databases: PubMed, Google Scholar and Ebsco. Literature is searched by keyword and Boolean operator (AND, OR, and NOT). Criteria for inclusion and exclusion of literature using PICOS strategy. Result: The journal's findings show educational videos and games can improve knowledge, dental and oral health attitudes, and teeth brushing skills. Conclusion:  Educational game media is more effective in improving knowledge, attitudes and actions of dental and oral hygiene. The advice for health workers is expected to provide dental health counseling using video or educational games in improving knowledge, attitudes and actions of brushing teethKeywords: media; video; educational games; behavior; brushing teeth Latar Belakang: Penyebab permasalahan kesehatan gigi dan mulut yaitu perilaku, perilaku yang sering mengabaikan kebersihan gigi dan mulut. Di indonesia menunjukkan perilaku menyikat gigi setiap hari sebesar 94,7%, tetapi hanya 2,8% yang menyikat gigi di waktu yang benar. Salah satu upaya dalam peningkatan derajat kesehatan gigi dan mulut yaitu dengan cara promotif atau promosi kesehatan. Dalam upaya promosi kesehatan untuk memudahkan penyampaian pesan atau informasi biasanya digunakan media. Banyak media yang dapat digunakan salah satunya media video dan game edukasi untuk membantu penyampaian informasi. Media juga termasuk dalam agen  sosialisasi yang dapat memberikan peran dalam mengembangkan dan memengaruhi perilaku seseorang. Metode: Penelitian ini bertujuan untuk mengetahuai efektivitas antara media video dan game edukasi tentang perilaku menyikat gigi. Jenis penelitian ini merupakan penelitian literature review. Data yang digunakan dalam penelitian literature review adalah data sekunder yang dapat diperoleh dari berbagai macam bentuk literature. Sumber data-data sekunder tersebut menggunakan 3 database yaitu: PubMed, Google Scholar dan Ebsco. Literatur dicari berdasarkan keyword (kata kunci) dan boolean operator (AND,OR, dan NOT). Kriteria inklusi dan ekslusi literatur menggunakan strategi PICOS. Hasil: temuan jurnal menunjukkan video dan game edukasi dapat meningkatkan pengetahuan, sikap kesehatan gigi dan mulut, dan keterampilan menggosok gigi. Kesimpulan: Media game edukasi lebih efektif dalam meningkatkan pengetahuan, sikap dan tindakan kebersihan gigi dan mulut. Adapun saran untuk bagi petugas kesehatan diharapkan perlu memberikan penyuluhan kesehatan gigi menggunakan video ataupun game edukasi dalam meningkatkan pengetahuan, sikap dan tindakan menyikat gigi.Kata Kunci: media; video; game edukasi; perilaku; menyikat gigi